1995
DOI: 10.1007/bf01474514
|View full text |Cite
|
Sign up to set email alerts
|

Neurotherapy for stroke rehabilitation: A single case study

Abstract: A 55-year-old male subject was treated with a two-tiered neurotherapy approach for a period of six months beginning approximately one year after a left-side CVA. Medical evaluation revealed left posterior temporal/parietal infarctions secondary to occlusion of the left internal carotid artery. The patient complained of hesitant speech with word finding difficulty and paraphasia, difficulty focusing his right eye, lack of balance and coordination, poor short-term memory, poor concentration, anxiety, depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 11 publications
6
71
0
5
Order By: Relevance
“…Overall, study designs and NFT therapy and training protocols were diverse and heterogeneous in nature. Five of the interventions were case studies [41][42][43][44][45]. Three controlled trials were also included [6,46]; two were non-randomized and non-blinded (experiment 1 n = 32, experiment 2 n = 17) [6], and one was randomized but non-blinded (n = 27) [46].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, study designs and NFT therapy and training protocols were diverse and heterogeneous in nature. Five of the interventions were case studies [41][42][43][44][45]. Three controlled trials were also included [6,46]; two were non-randomized and non-blinded (experiment 1 n = 32, experiment 2 n = 17) [6], and one was randomized but non-blinded (n = 27) [46].…”
Section: Resultsmentioning
confidence: 99%
“…6 months or more post-stroke) [41][42][43]. Two studies indicated participants were recruited from an inpatient rehabilitation hospital, possibly implying these participants were still in the sub-acute phase (i.e.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations